A Small Island With Big Differences? Folk Perceptions in the Context of Dialect Levelling and Koineization - Fotiou, Constantina; Grohmann, Kleanthes K. (Frontiers in Communication, 2022)
This paper presents the results of the first study within a perceptual dialectology framework in the Greek-speaking community in Cyprus. Thirty participants from three age groups of equal size took part in a sociolinguistic interview. As part of the language module component of the interview, they discussed their beliefs about regional variation in Cyprus and completed the so-called ‘draw-a-map task’. All participants were residents of urban areas of Nicosia, the capital of Cyprus. The Greek-speaking community in Cyprus is diglossic: Standard Modern Greek is the High variety, while Cypriot Greek—the mother tongue of Greek Cypriots—is the Low variety. The latter is currently undergoing levelling of marked local basilect features and subvarieties. A quantitative analysis of the maps demonstrates that some areas in Cyprus (mainly in the periphery) have a stronger sociolinguistic salience than others. At the same time, the participants’ own way of speaking is perceived as unmarked, neutral and one that enjoys wider acceptance over other regional dialects. This study also shows a clear preference for characterizing a (presumed) dialect area with linguistic characteristics, rather than with evaluative commentary contra many similar studies in the literature and suggests a number of reasons why this may be so. Overall, this research shows how studies on language perception can inform and complement studies on language production in a given community. The participants drew an average of just four regional areas on their maps and viewed the different cities and their districts, or combinations thereof, as the different regional dialect areas they perceive to exist in Cyprus. It is argued in this paper that the small number of areas drawn and the emphasis on urban sites are consistent with regional dialect levelling. Consistent with regional dialect levelling is also the finding that the participants’ linguistic description of regional variation, while mainly accurate, is superficial and lacks detail. Interestingly, many of the participants also seem to be well aware of regional dialect levelling in their community. Other studies in the literature do not really discuss speakers’ awareness of levelling and this should be further explored in future studies.